A Reconsideration of Gender Differences in Risk Attitudes - Antonio Filippin; Paolo Crosetto (Institute for the Study of Labor (IZA), 2014)
This paper reconsiders the wide agreement that females are more risk averse than males providing a leap forward in its understanding. Thoroughly surveying the experimental literature we first find that gender differences are less ubiquitous than usually depicted. Gathering the microdata of an even larger sample of Holt and Laury replications we boost the statistical power of the test and show that the magnitude of gender differences, although significant, is economically unimportant. We conclude that gender differences systematically correlate with the features of the elicitation method used and in particular the availability of a safe option and fixed probabilities.
Keywords: C81; C91; D81; 330; gender; risk; survey